Visual methods in social research - Marcus Banks; Zeitlyn, David (New Delhi Sage Publications, 2025)
Reading Pictures; Encountering the Visual; Material Vision; Research Strategies; Making Images; Presenting Research Results; Perspectives on visual Research
Keywords: Social Work